Distinct DNA Binding Sites Contribute to the TCF Transcriptional Switch in C. elegans and Drosophila - Bhambhani, Chandan; Ravindranath, Aditi J.; Mentink, Remco A.; Chang, Mikyung V.; Betist, Marco C.; Yang, Yaxuan X.; Koushika, Sandhya P.; Korswagen, Hendrik C.; Cadigan, Ken M. (PLoS genetics, 2014)
Regulation of gene expression by signaling pathways often occurs through a transcriptional switch, where the transcription factor responsible for signal-dependent gene activation represses the same targets in the absence of signaling. T-cell factors (TCFs) are transcription factors in the Wnt/ß-catenin pathway, which control numerous cell fate specification events in metazoans. The TCF transcriptional switch is mediated by many co-regulators that contribute to repression or activation of Wnt target genes. It is typically assumed that DNA recognition by TCFs is important for target gene location, but plays no role in the actual switch. TCF/Pangolin (the fly TCF) and some vertebrate TCF isoforms bind DNA through two distinct domains, a High Mobility Group (HMG) domain and a C-clamp, which recognize DNA motifs known as HMG and Helper sites, respectively. Here, we demonstrate that POP-1 (the C. elegans TCF) also activates target genes through HMG and Helper site interactions. Helper sites enhanced the ability of a synthetic enhancer to detect Wnt/ß-catenin signaling in several tissues and revealed an unsuspected role for POP-1 in regulating the C. elegans defecation cycle. Searching for HMG-Helper site clusters allowed the identification of a new POP-1 target gene active in the head muscles and gut. While Helper sites and the C-clamp are essential for activation of worm and fly Wnt targets, they are dispensable for TCF-dependent repression of targets in the absence of Wnt signaling. These data suggest that a fundamental change in TCF-DNA binding contributes to the transcriptional switch that occurs upon Wnt stimulation.